(untitled) (Journal of Partial Differential Equations, 2025)
We consider the following Schrödinger-Newton system with negative critical nonlocal term where a and f satisfy some certain conditions. By using the variational method and analytical techniques, we obtain the existence of positive ground state solutions which improves the recent results in the literature.